2006
DOI: 10.1097/01.mnm.0000189781.62282.0d
|View full text |Cite
|
Sign up to set email alerts
|

Intra-individual comparison of sentinel lymph node scintigraphy on the day of injection and on the following day in breast cancer

Abstract: Our study demonstrated that for patients undergoing the 2-day protocol for sentinel node procedure in early stage breast cancer, the optimal imaging time would be to perform lymphoscintigraphy 1 h after injection, with the possibility of imaging patients the following day in cases where lymphoscintigraphy was negative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 19 publications
1
20
0
1
Order By: Relevance
“…In three patients, SLN was not detected on 30-min image, and it could not be detected at all even on the delayed images either (up to 180 min). Limited studies also showed that sensitivity of imaging is not significantly different in early and delayed images and almost all of the SLNs are visible on the early images [14][15][16]26]. The type of the radiotracer as well as the optimal time of imaging is largely determined by operating room scheduling.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…In three patients, SLN was not detected on 30-min image, and it could not be detected at all even on the delayed images either (up to 180 min). Limited studies also showed that sensitivity of imaging is not significantly different in early and delayed images and almost all of the SLNs are visible on the early images [14][15][16]26]. The type of the radiotracer as well as the optimal time of imaging is largely determined by operating room scheduling.…”
Section: Discussionmentioning
confidence: 94%
“…Injection site [20] and dose [21], type of the radiotracer [21,22], and patient eligibility are among these controversies [23]. Interestingly, different techniques of SLN biopsy usually have comparable results for reliable SLN detection [14].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Because of time constraints the coordination of lymphoscintigraphy with surgery may be difficult to achieve [15][16][17][18]. The results of this study showed that there was a high-identification rate of sentinel lymph nodes, 91.1% by lymphoscintigraphy and 89.7% by gamma probe with the 1 day protocol.…”
Section: Discussionmentioning
confidence: 91%